2017
DOI: 10.1039/c7dt03265j
|View full text |Cite
|
Sign up to set email alerts
|

Novel half-sandwich iridium(iii) imino-pyridyl complexes showing remarkable in vitro anticancer activity

Abstract: Seven novel half-sandwich Ir cyclopentadienyl complexes, [(η-Cp)Ir(N^N)Cl]PF, have been prepared and characterized, where Cp is Cp* or the biphenyl derivative Cp (CMeCHCH), and the N^N-chelating ligands are imino-pyridyl Schiff-bases. The X-ray crystal structures of complexes 2A, 2B, and 3A have been determined. Excitingly, most of the complexes show potent antiproliferative activity towards A549 and HeLa cancer cells, except for Cp* complex 1A towards HeLa cells. Cp complex 2B displayed the highest potency, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 53 publications
7
73
1
Order By: Relevance
“…The antiproliferative activity of 3C was evaluated against the normal cell line BEAS‐2B (human bronchial epithelial cells) with IC 50 value of 3.8 μM, suggesting no selectivity between cancer and normal cells (Table ). We have reported half‐sandwich iridium complexes containing N^N‐chelating iminopyridyl ligands that displayed highly potent antiproliferative activity against cancer cells, but poor cytotoxic selectivity between cancer and normal cells . Substitution of cyclopentadienyl iridium moiety with ruthenium benzene led to a decrease of potency but better cytotoxic selectivity, suggested that the metals play a vital role in anticancer activity.…”
Section: Resultsmentioning
confidence: 99%
“…The antiproliferative activity of 3C was evaluated against the normal cell line BEAS‐2B (human bronchial epithelial cells) with IC 50 value of 3.8 μM, suggesting no selectivity between cancer and normal cells (Table ). We have reported half‐sandwich iridium complexes containing N^N‐chelating iminopyridyl ligands that displayed highly potent antiproliferative activity against cancer cells, but poor cytotoxic selectivity between cancer and normal cells . Substitution of cyclopentadienyl iridium moiety with ruthenium benzene led to a decrease of potency but better cytotoxic selectivity, suggested that the metals play a vital role in anticancer activity.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14] In particular, there have been several attempts to use Ir-based carbene compounds or complexes as antitumor agents; a series of half-sandwich Ir(III) complexes were synthesized or modeled and reported as potential anticancer drugs. [15][16][17][18][19][20] Indeed, one can expect for the new Ir(III) complexes, as well as for other metallodrugs, to (i) get stronger and more selective effects against tumors, (ii) extend the spectrum of cancer treatment and (iii) overcome the limits of Pt-based drugs such as the platin resistance and other severe side-effects.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of base pairs of DNA with complexes usually involves intercalation, interaction, non-intercalative electrostatic interactions as wella sd amage of the DNA double helix. [42][43][44][45] The change in the absorption wavelength of the as-synthesized complexes as the amount of CT-DNA (DNA sodium from calf thymus) increased was determined by means of UV/Vis titration, and the bindingc onstants( K b )o ft he complexes were also calculated. The role of metal iridium in our complexes is probablyt op rovideacoordination center.…”
Section: Interaction With Ct-dnamentioning
confidence: 99%